Photothermal Therapy: pH‐Responsive Fe(III)–Gallic Acid Nanoparticles for In Vivo Photoacoustic‐Imaging‐Guided Photothermal Therapy (Adv. Healthcare Mater. 7/2016). Issue 7 (April 2016) - Zeng, Jianfeng; Cheng, Ming; Wang, Yong; Wen, Ling; Chen, Ling; Li, Zhen; Wu, Yongyou; Gao, Mingyuan; Chai, Zhifang
Abstract : On page 772 Z. Li, Y. Y. Wu, M. Y. Gao and co‐workers show that a tumor‐specific phototherapeutic agent can be created from pH‐responsive Fe(III)‐gallic‐acid nanoparticles. Since the particles can be monitored by photoacoustic imaging, show low toxicity, and are readily degraded in non‐tumor tissue, they represent a promising new way of designing theranostic agents.